Brain Metastases from Ovarian Carcinoma. (1st December 2011) - Piura, Ettie; Piura, Benjamin
Abstract : This paper will focus on knowledge related to brain metastases from ovarian carcinoma. So far, less than 600 cases were documented in the literature with an incidence among ovarian carcinoma patients ranging from 0.29% to 11.6%. The ovarian carcinoma was usually an advanced-stage epithelial serous carcinoma, and the median interval between diagnosis of ovarian carcinoma and brain metastases was 2 years. Most often, brain metastases, affected the cerebrum, were multiple and part of a disseminated disease. Treatment of brain metastasis has evolved over the years from whole brain radiotherapy (WBRT) only to multimodal therapy including surgical resection or stereotactic radiosurgery followed by WBRT and/or chemotherapy. The median survival after diagnosis of brain metastases was 6 months; nevertheless, a significantly better survival was achieved with multimodal therapy compared to WBRT only. It is suggested that brain imaging studies should be included in the followup of patients after treatment for ovarian carcinoma.